Pengaruh Profitabilitas, Likuiditas dan Growth Opportunity Terhadap Struktur Modal (Pada Perusahaan Food and Beverage yang Terdaftar di BEI Periode 2015-2017) - Olla Fathimatuz Zahro; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to determine the effect of profitability, liquidity and growth opportunity on the capital structure. This study uses Explanatory Research. The population in this study were all Food and Beverage companies listed on the Indonesia Stock Exchange for the period of 2015 until the end of 2017, and a sample of 13 companies. Methods of collecting data through library methods and documentation methods. Analysis of the data used is multiple linear regression analysis. In this study the data analysis used was using SPSS version 20. The sampling technique in this study used a purposive sampling method using several criteria. Data testing techniques in this study include: normality test, classic assumption test and multiple linear regression analysis, and hypothesis testing. The results of this study indicate that: (1) profitability has a positive effect on capital structure, (2) liquidity has a negative effect on capital structure and (3) growth opportunity has a positive effect on capital structure. Keywords : Profitability, Liquidity, Growth Opportunity and Capital Structure.